2013
DOI: 10.1111/ecge.12027
|View full text |Cite
|
Sign up to set email alerts
|

A Fetish and Fiction of Finance: Unraveling the Subprime Crisis

Abstract: As the moderately strengthened financial regulation of Basel III comes into effect over the next seven years, this article sets out a cautionary reminder as to why regulation needs to move beyond a focus on the mitigation and distribution of risk. To do so, the article unravels the much-misunderstood experiences of eight Norwegian municipalities whose investments plummeted as the subprime crisis unfolded: investments that had no immediate ties to subprime mortgage lending or mortgage-backed securities. Focusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 42 publications
0
18
0
4
Order By: Relevance
“…These asset‐rich organizations were confronted with a changing financial landscape that increasingly provided them with instruments to use their balance sheets in unconventional ways to lower costs or increase income. The financialization of Dutch housing associations is therefore more a tale of opportunities than one of constraints, comparable to the tale of Norwegian municipalities that transformed revenues from their hydroelectric resources into complex and risky financial investments (Aalbers, ; Pani and Holman, ).…”
Section: Introductionmentioning
confidence: 99%
“…These asset‐rich organizations were confronted with a changing financial landscape that increasingly provided them with instruments to use their balance sheets in unconventional ways to lower costs or increase income. The financialization of Dutch housing associations is therefore more a tale of opportunities than one of constraints, comparable to the tale of Norwegian municipalities that transformed revenues from their hydroelectric resources into complex and risky financial investments (Aalbers, ; Pani and Holman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Flere kraftige fall i kraftprisene rundt årtusenskiftet hadde gjort planlegging vanskelig og kommuneøkonomien sårbar. Kontraktene med Terra var i stor grad et forsøk på å sikre stabilitet og redusere usikkerhet knyttet til kommunenes avhengighet av denne typen markedsfluktuasjoner (Løding, 2018;Pani & Holman, 2014). Begge steder ble kontraktene vurdert å vaere tilnaermet risikofrie.…”
Section: Når Finansmarkedene Kommer Inn I Den Kommunale Varmenunclassified
“…(Wainwright 2011(Wainwright , p. 1301. For example, Marshall, Pike, et al (2011) showed how the September 2007 run on Northern Rock resulted from the interplay between global financial centres and peripheral financial hubs such as Newcastle, and then deepened development in the urban landscape; Pani and Holman (2013) showed how even localities at a "fictitious distance" from global booms and bustssuch as Norwegian municipalitieswere entangled in the crisis due to intertwined crossborder financial cash-flows; and Hendrikse and Sidaway (2014) showed how the German city of Pforzheim experienced crisis-linked losses due to derivative contracts it had signed with Duetsche Bank.…”
Section: Geographers On Subprime Lending and Crisismentioning
confidence: 99%